Arbóreas nativas e substratos amenizantes da contaminação do solo com cobre - Grolli, Andre Luís (2016)
More contaminated areas with copper were discovered and this had contributed negatively for plants establishment, so more studies are need to reutilize this areas. Thus, the objective of this work is to enable the attenuation of the contamination on native woody seedlings production in contaminated soil with copper. Three experiments were realized. The first involving the evaluation of the growth and quality of Bauhinia forficata Link, Pterogyne nitens Tul and Enterolobium contortisiliquum Vell. seedlings in soil with dosis of copper. On the second work, the effect of broiler litter was evaluated on soil chemical attributes and the growth of E. contortisiliquum seedling. On the third, the effect of broiler litter (CA) and mix of broiler litter with commercial substrate (CA+SC) evaluated to attenuation of copper contamination in soil and E. contortisiliquum potential to descontamination the soil. E. contortisiliquum had more tolerance to high copper dosis than B. forficate and P. nitens. The addition of 36% of CA on the SC and 33% on the peat enables increasing on morphological parameters of E. contortisiliquum seedlings. The utilization of the CA+SC was efficient to attenuation of the copper contamination. The morphological parameters was stimulated by the addition of the mix, with better results in 20 and 30% in contaminated soil with 400 mg of kg-1 of soil.